The discordance of governance performance from environmental and social performance on idiosyncratic risk: The effect of board composition - Xin, Yang; Sheikh Hassan, Ahmad Fahmi; Wei Lau, Theng Lau; Ab Razak, Nazrul Hisyam (Taylor and Francis, 2023)
In recent years, the nexus between environmental, social, and governance (ESG) factors and financial performance has been a focal point of academic discourse. While much of the existing literature emphasizes the potential positive correlations between ESG performance and financial gains, ambiguities persist, especially concerning the governance pillar. Against this backdrop, our study delves into the relationship between ESG performance and idiosyncratic volatility, utilizing a comprehensive panel dataset of U.S. listed companies spanning 2005 to 2019. Through analytical methodologies like the two-stage least square method with instrumental variables (2SLS-IV) and the dynamic Generalised Method of Moments (GMM), we unveil an intriguing discovery: governance performance does not significantly correlate with idiosyncratic volatility, whereas environmental and social performance demonstrate a strong negative linkage. This deviation from conventional wisdom underscores our study’s unique contributions. We shed light on the governance factor’s discordance from its environmental and social counterparts in shaping firm-specific risk, introduce the emerging concept of board composition’s moderating effects on the ESG-volatility relationship, and present a holistic perspective by covering an extensive array of U.S. sectors. Our findings carry profound implications for the future trajectory of sustainable investing and corporate governance practices.